Acquisition and Assimilation of Nitrogen as Peptide-Bound and D-Enantiomers of Amino Acids by Wheat - Hill, Paul W. (Public Library of Science, 2011)
Nitrogen is a key regulator of primary productivity in many terrestrial ecosystems. Historically, only inorganic N (NH(4) (+) and NO(3) (-)) and L-amino acids have been considered to be important to the N nutrition of terrestrial plants. However, amino acids are also present in soil as small peptides and in D-enantiomeric form. We compared the uptake and assimilation of N as free amino acid and short homopeptide in both L- and D-enantiomeric forms. Sterile roots of wheat (Triticum aestivum L.) plants were exposed to solutions containing either (14)C-labelled L-alanine, D-alanine, L-trialanine or D-trialanine at a concentration likely to be found in soil solution (10 µM). Over 5 h, plants took up L-alanine, D-alanine and L-trialanine at rates of 0.9±0.3, 0.3±0.06 and 0.3±0.04 µmol g(−1) root DW h(−1), respectively. The rate of N uptake as L-trialanine was the same as that as L-alanine. Plants lost ca.60% of amino acid C taken up in respiration, regardless of the enantiomeric form, but more (ca.80%) of the L-trialanine C than amino acid C was respired. When supplied in solutions of mixed N form, N uptake as D-alanine was ca.5-fold faster than as NO(3) (-), but slower than as L-alanine, L-trialanine and NH(4) (+). Plants showed a limited capacity to take up D-trialanine (0.04±0.03 µmol g(−1) root DW h(−1)), but did not appear to be able to metabolise it. We conclude that wheat is able to utilise L-peptide and D-amino acid N at rates comparable to those of N forms of acknowledged importance, namely L-amino acids and inorganic N. This is true even when solutes are supplied at realistic soil concentrations and when other forms of N are available. We suggest that it may be necessary to reconsider which forms of soil N are important in the terrestrial N cycle.